New and future developments in catalysis : solar photocatalysis - Suib, Steven L., 1953- (Elsevier, 2013)
New and Future Developments in Catalysis is a package of seven books that compile the latest ideas concerning alternate and renewable energy sources and the role that catalysis plays in converting new renewable feedstock into biofuels and biochemicals. Both homogeneous and heterogeneous catalysts and catalytic processes will be discussed in a unified and comprehensive approach. There will be extensive cross-referencing within all volumes. The use of solar energy during various catalytic chemical processes for the production of an array of chemical products is the theme of this volume. Photocatalysis is a topic of increasing importance due to its essential role in many of today's environmental and energy source problems. The use of solar energy for catalytic reactions results in a carbon dioxide-neutral process. All photocatalytic processes and the future developments in this area are discussed, including an economic analysis of the various processes. Offers in-depth coverage of all catalytic topics of current interest and outlines future challenges and research areas. A clear and visual description of all parameters and conditions, enabling the reader to draw conclusions for a particular case. Outlines the catalytic processes applicable to energy generation and design of green processes.